Dynamic Characteristic Analysis of Antibodies in Patients With COVID-19: A 13-Month Study - Shi, Danrong; Weng, Tianhao; Wu, Jie; Dai, Chunyan; Luo, Rui; Chen, Keda; Zhu, Miaojin; Lu, Xiangyun; Cheng, Linfang; Chen, Qiuqiang; Liu, Fumin; Wu, Zhigang; et al. (Frontiers in Immunology, 2021)
There is a worldwide pandemic of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection; yet our understanding remains limited on the characteristic of antibodies, especially for dynamic long-term tracking. Sequential serum samples were collected up to 416 days post onset of symptoms (POS) from 102 patients with coronavirus disease 2019 (COVID-19). Immunoglobulin (Ig)G, IgM, and IgA levels targeting SARS-CoV-2 spike 1 receptor-binding domain (S1-RBD), spike 2 extracellular domain (S2-ECD), and nucleocapsid protein (N) were quantified as well as neutralizing activity. We were pleasantly surprised to find that the antibody remained detective and effective for more than a year POS. We also found the varied reactions of different antibodies as time passed: N-IgA rose most rapidly in the early stage of infection, while S2-IgG was present at a high level in the long time of observation. This study described the long traceable antibody response of the COVID-19 and offered hints about targets to screen for postinfectious immunity and for vaccination development of SARS-CoV-2.